Qualitative assessment of faculty’s perspectives regarding effective implementation of competency-based medical education - Noopur S. Nagar; Shashwat S. Nagar (Indian Journal of Community and Family Medicine)
Introduction: It has been just over four years since the implementation of competency-based medical education (CBME) and it is opined that medical education has undergone a paradigm shift. With the inception of CBME, the focus has shifted from a traditional trainer-based approach to a newer learner-based approach. The role of medical teachers has also shifted from being a traditional teacher to being a facilitator for the implementation of the program. The trainer’s perspectives and qualitative assessment of the implementation of the new program are less explored. The study was planned to carry out a qualitative assessment of faculty members’ perspectives regarding the new competency-based medical curriculum with respect to their perceived challenges and many reservations about its effective implementation in the future. Material and Methods: A qualitative study was conducted, which included in-depth interviews of medical faculty members. The faculty members selected were from all three categories, i.e. pre, para, and clinical subjects. Data were collected after preparing a guide for in-depth interviews and obtaining consent from them. A rapporteur was appointed to make a note of the verbatim and themes were generated on the basis of the responses provided. Content analysis was carried out from the responses of the faculty members. Results: A total of nine themes were generated on the basis of content analysis. Most faculty members believed that CBME was more structured and had clear objectives and better documentation. However, they felt it was more resource-intensive and needed better planning and resources for better implementation. Faculty members perceived the strengths of the new curriculum along with its challenges in implementation and felt that in order to make it a success, there is a need for better planning and capacity building. Conclusion: Even though CBME is in its early stages, the curriculum structure appears promising to most faculty members. Qualitative assessments of similar types in different institutes across the country can help in evaluating and successfully implementing CBME in the future.